Perilaku Petani dalam Menghadapi Fluktuasi Harga Sawit Menurut Perspektif Ekonomi Syariah - Ismiati, Ismiati; Lubis, Haniah (JAWI : Journal of Ahkam Wa Iqtishad, 2023)
The frequently fluctuating price of palm oil causes palm oil farmers in Tanjung Kudu, Kualu Village, to take action to overcome their family's economic problems as a result of prices fluctuating drastically. The aim of this research is to determine the behavior of oil palm farmers in facing price fluctuations and to determine the Islamic economics review of the behavior of oil palm farmers in facing price fluctuations in Tanjung Kudu, Kualu Village. This research is field research located in Tanjung Kudu, Kualu Village. The informants in this research were 10 oil palm farmers with the criteria being farmers who had a plantation area of more than 2 hectares and had worked for a minimum of 5 years. Data collection techniques through observation, interviews and documentation. Data analysis is descriptive qualitative. It was found that oil palm farmers carry out various kinds of behavior to increase family income, such as working side jobs, becoming farm laborers, construction workers, traders, and others. Some of the oil palm farmers' wives also help in increasing the family's income by opening small businesses such as opening a breakfast business, a daily shop business, and a laundry business. The behavior of oil palm farmers in facing price fluctuations applies the principle of honesty, always trying to earn a living, not being discouraged, never giving up, being responsible for family needs, and not being lazy in working.